2021
DOI: 10.1021/acs.chemrev.1c00793
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress and Future Prospects on All-Organic Polymer Dielectrics for Energy Storage Capacitors

Abstract: With the development of advanced electronic devices and electric power systems, polymer-based dielectric film capacitors with high energy storage capability have become particularly important. Compared with polymer nanocomposites with widespread attention, all-organic polymers are fundamental and have been proven to be more effective choices in the process of scalable, continuous, and large-scale industrial production, leading to many dielectric and energy storage applications. In the past decade, efforts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
230
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(232 citation statements)
references
References 481 publications
2
230
0
Order By: Relevance
“…[34,35] In parallel to the organic/inorganic polymer nanocomposites, all-organic multiphase polymeric dielectrics have been reported for the improvement of energy storage performances. [36] For the fabrication of all-organic multiphase dielectrics, two miscible dielectric polymers with respective advantages can be directly mixed or blended; [37][38][39][40][41] on the other hand, one organic component can be incorporated as fillers or coated as the surface layer for another matrix polymer, [42,43] which have been demonstrated as effective approaches to tune the electrical displacement and breakdown behaviors of polymers. For instance, more recently, it has been demonstrated that the introduction of a polymethyl methacrylate nano-layer onto the surface of PVDF film enables modified surface defects and increased Young's modulus, leading to remarkably improved breakdown strength of 767.05 kV mm −1 in the PVDF-based all-organic dielectric polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] In parallel to the organic/inorganic polymer nanocomposites, all-organic multiphase polymeric dielectrics have been reported for the improvement of energy storage performances. [36] For the fabrication of all-organic multiphase dielectrics, two miscible dielectric polymers with respective advantages can be directly mixed or blended; [37][38][39][40][41] on the other hand, one organic component can be incorporated as fillers or coated as the surface layer for another matrix polymer, [42,43] which have been demonstrated as effective approaches to tune the electrical displacement and breakdown behaviors of polymers. For instance, more recently, it has been demonstrated that the introduction of a polymethyl methacrylate nano-layer onto the surface of PVDF film enables modified surface defects and increased Young's modulus, leading to remarkably improved breakdown strength of 767.05 kV mm −1 in the PVDF-based all-organic dielectric polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, they are typically used in small electronic components such as polymer film capacitors and flexible wearable electronic devices. Dielectric capacitors have been widely utilized in many fields, such as microwave communication, pulse energy system, sustainable energy system, and electric vehicles, 125 as shown in Figure 10. Polymer film capacitors have the advantages of low dielectric loss, stable current density, and long service life 126 .…”
Section: Applications and Feasibilitiesmentioning
confidence: 99%
“…Application fields of dielectric capacitors 125 . Copyright 2021, American Chemical Society [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Applications and Feasibilitiesmentioning
confidence: 99%
“…Polymers are multifunctional materials that can be alternatives to other materials such as metals, glass, and other traditional materials [1][2][3][4][5]. They can be pure organic [6][7][8][9] or hybrid materials including coordination polymers or metal-organic frameworks (MOFs) [10,11,20,[12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%